The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1149/2162-8777/ab8f19
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Ray and Neutron Radiation Effects on the Electrical and Structural Properties of n-ZnO/p-CuGaO2 Schottky Diode

Abstract: Solar assisted heat pump (SAHP) system integrates a solar thermal energy source with a heat pump. This technique is a very fundamental concept, especially for drying applications. By combining a solar thermal energy source such as solar thermal collectors and a heat pump dryer will assist in reducing the operation cost of drying and producing products with high quality. Many review papers in the literature evaluated the R&D aspects of solar-assisted heat pump dryers (SAHPD). This critical review paper studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 63 publications
(83 reference statements)
0
3
0
Order By: Relevance
“…The series resistance, "RS", and the ideality factor, "n", are crucial parameters that indicate the electrical characteristics of the diodes. These values can be determined using the equation [2,16,17]:…”
Section: Mathematical Approach On the Extraction Of Schottky Diode Pa...mentioning
confidence: 99%
See 2 more Smart Citations
“…The series resistance, "RS", and the ideality factor, "n", are crucial parameters that indicate the electrical characteristics of the diodes. These values can be determined using the equation [2,16,17]:…”
Section: Mathematical Approach On the Extraction Of Schottky Diode Pa...mentioning
confidence: 99%
“…Additionally, atomic displacement, which results from irradiation and produces primary knock-on atoms (PKA), leads to lattice defects [22,23,24]. Studies have shown that exposure of ZnO-based semiconductors to gamma radiation results in a deterioration of their electrical parameters, as evidenced by a decrease in turn-on voltage, which is caused by structural defects present in the semiconductor, leading to an increase in its ideality factor [1,2,24,25]. These alterations can also be attributed to the combined effects of the creation of interface states and the generation of electron-hole pairs in the insulating layer.…”
Section: Steady State Analysismentioning
confidence: 99%
See 1 more Smart Citation